2017
DOI: 10.1183/23120541.00019-2016
|View full text |Cite
|
Sign up to set email alerts
|

Importance of serial changes in biomarkers in idiopathic pulmonary fibrosis

Abstract: The clinical significance of serial changes in serum biomarkers in patients with idiopathic pulmonary fibrosis (IPF) remains to be established. This retrospective study was conducted to clarify the associations of serial changes in serum Krebs von den Lungen-6 (KL-6) and surfactant protein-D (SP-D) with changes in physiological indices and overall mortality in IPF.The study subjects were 75 patients with IPF. The 6 month change in serum KL-6 was significantly correlated with changes in the percentage of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…Since KL-6 is more highly expressed in injured or regenerating epithelial cells than in normal epithelial cells [15,16], KL-6 could be used as a biomarker of lung injury. Previous studies showed that KL-6 might be a useful biomarker in evaluation of disease severity, and prediction of prognosis in patients with IPF [17][18][19][20]. In the case of RA-ILD, Kinoshita et al reported that KL-6 levels are correlated with the extent of the reticular opacities or total disease extent on HRCT in 47 patients with RA-ILD [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since KL-6 is more highly expressed in injured or regenerating epithelial cells than in normal epithelial cells [15,16], KL-6 could be used as a biomarker of lung injury. Previous studies showed that KL-6 might be a useful biomarker in evaluation of disease severity, and prediction of prognosis in patients with IPF [17][18][19][20]. In the case of RA-ILD, Kinoshita et al reported that KL-6 levels are correlated with the extent of the reticular opacities or total disease extent on HRCT in 47 patients with RA-ILD [21].…”
Section: Introductionmentioning
confidence: 99%
“…The expression level of KL-6 signi cantly increases in alveolar tissue affected by interstitial pneumonia and enters the blood circulation through the damaged alveoli [6]. The alveolar surface protein SP-A, which is synthesized and secreted by airway and alveolar epithelial cells, is an important marker of alveolar injury [7,8]. In Japan [9,10], serum KL-6, SP-A and SP-D levels are widely used as biomarkers for the diagnosis and prognosis of idiopathic pulmonary brosis and ILD.…”
Section: Surfactant Protein-a (Sp-a) Andmentioning
confidence: 99%
“…However, on the other hand, some patients experience an accelerated clinical and functional deterioration [3] that could represent another phenotype. Rapid progressors have been associated with low FVC and DLCO as well as with the upregulation of several genes such as those involved in cell motility, myofibroblast differentiation, coagulation, oxidative stress, and development, among them TLR9 , CCL18 , antibodies against HSP70 , and KL-6 [65]. Lung microbiome has also been related to a faster deterioration of lung function [66]…”
Section: Phenotypesmentioning
confidence: 99%